Electronic Pad To Paragliding Landing Score System Based Internet Of Things (IOT) - Venezia Ferly Wiranda; Yohandri (Department of Physics, Universitas Negeri Padang, 2023)
Advances in technology allow sports equipment to become more efficient, easier to use, and have more use value. One of the technological advancements in the field of paragliding is the existence of a tool that can measure paragliding accuracy scores without having to measure them manually. However, this tool is still difficult to obtain because the price is expensive and the diameter is still 22 cm, so if a paragliding athlete lands outside the tool it is still measured manually. Therefore, an Internet of Things (IoT) based electronic pad with a diameter of 100 cm was developed. This electronic pad is designed to use a push button as a detector to get a paragliding screening accuracy score and a Radio Frequency Identification (RFID) sensor is used to detect the identity code of the intended athlete. The output of the tool appears on Google Sheets and in the Android application to make it easier to record scores for the superior accuracy of paragliding athletes. The type of research used is engineered research, namely research that applies knowledge in the form of tool design or design. The direct result of the research is the measurement of the heart rate score and the identity code of the paragliding athlete and for the indirect measurement results in the form of the accuracy of the electronic pad device is 1 and the accuracy of the tool is 1. Based on the results of its accuracy and precision, this electronic pad tool is suitable for measuring landing accuracy scores and paragliding athlete identity codes.